Polityka rolna rządu Józefa Piłsudskiego (2 X 1926–12 VI 1928) - Łapa, Małgorzata (Zeszyty Wiejskie, 2017)
During the period of the prime minister's office by Józef Piłsudski, agricultural policy focused on activities aimed at protecting the consumer's interests. As a result, it focused on activities aimed at regulating the prices of agricultural commodities, mainly cereals. Such regulation by means of export restrictions contributed to a sharp fall in cereal prices. Regulation of trade in agricultural products did not positively affect the amplitude of price fluctuations. The reason for this was the undecided government export and import measures. Frequent changes caused anxiety among sellers and buyers, which caused that the price differences paid by producers and consumers significantly increased. Therefore, this policy encountered serious resistance from the landowners' spheres, merchants, as well as grain millers, who were also trade with grain. The attempt to develop a comprehensive plan of aid to agriculture was undertaken only at the turn of 1929 and 1930. The government's actions aimed at intensifying agricultural production did not bring good results. Eventually, they were stopped by the economic crisis.